Dispersal of cellulose fibers and metals from contaminated sediments of industrial origin in an estuary. (November 2020) - Apler, Anna; Snowball, Ian; Josefsson, Sarah
Abstract: The boreal forest's pulp and paper industry plays a major role in economic prosperity but, historically, caused an environmental burden. Remnants of discharges of contaminated suspended solids (fiberbanks) are continuously being discovered on the beds of shallow seas, rivers and lakes in the northern hemisphere. We investigated the dispersion of Cd, Cr, Cu, Hg, Ni, Pb and Zn from deeper to surficial layers in fiberbanks in a Swedish estuary and the larger-scale transport of the same metals to distal areas of sediment accumulation. We also tested the C:N ratio as a common denominator for these anthropogenic, cellulose-rich deposits. Sampling and analyses of three fiberbanks located in the inner part of the estuary and from sediment accumulation sites outside and along the estuary reveals that metal concentrations are regressing to background levels towards the surface at the accumulation sites. The fiberbanks show a higher degree of contamination and C:N ratios demonstrate inclusion of cellulose fibers. C:N ratios also indicate that there is currently no significant transport of fiberbank material into the distal areas. A ∼10 cm natural cap of recently settled fine-grained sediment covering one of the fiberbanks seems to prevent metals dispersing into overlying water whereas the other two fiberbanks show signs of metal enrichment and potential mercury methylation in surficial layers. Although the estuarine system seems to recover from the impact of industrial waste, there is no evidence that the fiberbanks will be remediated naturally but instead will continue to threaten the aquatic environment. Graphical abstract: Image 1 Highlights: Metal concentrations decrease towards the sediment surface in the impacted estuary. Deeper layers in fiberbanks are generally more contaminated than surficial layers. A ∼10 cm natural cap of over a fiberbank shields the water body from metal contaminants. A < ∼5 cm cap of fine-grained sediment does not form an effective natural cap. Fiberbanks may be local hotspots of legacy contaminants.